Design of experiments and discrete-event simulation to study oncology nurse workload. Issue 1 (2nd January 2020) - Baril, Chantal; Gascon, Viviane; Miller, Jonathan
Abstract: Due to the increasing number of cases of cancer, medical clinics specialized in cancer treatments must operate differently to meet demand. Besides growth in demand, research on cancer treatment has led to more complex chemotherapy protocols. The literature lists more than 170 chemotherapy protocols. However, in practice only a few are administered. In oncology, nurse-patients ratios and the treatment protocol to administer have an impact on nurse workload. The nurse-patients ratio is usually one nurse for four patients (1:4); meaning that the nurse administers treatments to four patients simultaneously. Delivering a chemotherapy treatment requires that the nurse performs different tasks according to the protocol. This research studies nurse workload related to the administration of chemotherapy treatments. Both physical and mental nurse workload are studied. We present an original quantitative approach based on discrete event simulation to measure nurse workload. It demonstrates that all protocols do not result in similar workloads. Our study shows that both physical and mental nurse workload should be taken into account in determining the nurse-patient ratio for the administration of chemotherapy treatment.